Economy of creativity in Stevens’s “Thirteen Ways of Looking at a Blackbird” and “Six Significant Landscapes” - Muhssen, Lina; Pirnajmuddin, Hossein; Amirian, Zahra; Ladani, Zahra Jannessari (Penerbit Universiti Kebangsaan Malaysia, 2025)
A man of business and poetry, Wallace Stevens is a peculiar master who combined a love of poetry and money in his life, overriding the gap between literature and economy, imagination and reality. Examining "Thirteen Ways of Looking at a Blackbird" and "Six Significant Landscapes" in the light of New Economic Criticism, we attempt to expound on the different rhetorical techniques and particular language and style Stevens has used to create an artistic product with economic value. We seek to explicate how Stevens's interest in money, power, prestige, and security as an insurance-poet man pertains to the accumulation of various types of capital ‒ cultural, economic, social and symbolic in Bourdieu’s sociological framework. Also examined is how Stevens borrows artistic devices/conventions ‒ like light/shadow imagery, repetition and geometric shapes ‒ from painting schools like impressionism, cubism and oriental paintings to ensure the exchange value of his poetry in the modernist marketplace. Furthermore, this interdisciplinary study explores the relationship between language and the economic system, focusing on Stevens's particular economy of language displayed in simple, short, declarative and ironic statements; the economy of imagery is present in precise and sharp images and haiku forms as it appears in imagism; and economy of space pictured in simple locations. The exchange between ideologies of the East and West also merits special attention.